Laser-induced modification of an excited-state vibrational wave packet in neutral H_{2} observed in a pump-control scheme - Gergana D. Borisova; Paula Barber Belda; Shuyuan Hu; Paul Birk; Veit Stooß; Maximilian Hartmann; Daniel Fan; Robert Moshammer; Alejandro Saenz; Christian Ott; Thomas Pfeifer (Physical Review Research)
We observe and modify a molecular vibrational wave packet in an electronically excited state of the neutral hydrogen molecule. In an extreme-ultraviolet (XUV) time-domain absorption spectroscopy experiment, we launch a vibrational wave packet in the D^{1}Π_{u}3pπ state of H_{2} and track its time evolution via the coherent dipole response. The reconstructed time-dependent dipole from experimentally measured XUV absorption spectra provides access to the revival of the vibrational wave packet, which we control via an intense near-infrared (NIR) pulse. Tuning the intensity of the NIR pulse, we observe the revival of the wave packet to be significantly modified, which is supported by the results of a multilevel simulation as well as an analytical model based on state-specific phase shifts. The NIR field is applied only 7 fs after the creation of the wave packet but influences its evolution up to at least its first revival at 270 fs. This experimental approach for nonlocal-in-time laser modification of quantum dynamics in a pump-control scheme enabled by molecular self-probing is generally applicable to a large range of molecules and materials as it only requires the observation of absorption spectra.